Effects of Preoperative Biopsies on Recurrence in Head and Neck Skin Cancer - Jung, Ji Eun (The Korean Society of Plastic and Reconstructive Surgeons, 2012)
BACKGROUND: Skin cancer is the most common malignant tumor in humans. Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the two most common types of skin cancers. When skin cancer is clinically suspected, preoperative biopsies are recommended for a definite diagnosis. However, despite a concern over potential increased risk of metastasis associated with mechanical manipulation, there have been few investigations into whether a preoperative biopsy affected the recurrence of BCC and SCC. METHODS: Primary BCC or SCC patients who underwent standard surgical excision from 1991 to 2010 were reviewed and a retrospective analysis was performed. Ultimately, 45 BCC patients and 54 SCC patients, who did not meet the exclusion criteria, were analyzed. To identify whether a preoperative biopsy affected the recurrence of BCC and SCC, the recurrence rates of each with and without biopsy were compared. RESULTS: Preoperative biopsy had no statistically significant effect on recurrence (BCC, P=0.8680; SCC, P=0.7520). Also, there was no statistical significance between the interval from initial biopsy to first operation and recurrence (BCC, P=0.2329; SCC, P=0.7140). Even though there was no statistical significance, the mean interval from the biopsy to the operation among the BCC patients who underwent preoperative biopsy was 9.2 months in those who had recurrence and 2.0 months in those who had no recurrence. CONCLUSIONS: There was no statistically significant relationship between preoperative biopsy and recurrence of BCC and SCC. However, there was a tendency toward recurrence in patients with a longer interval between the biopsy and the corrective operation in BCC.